International Corporate Brand Management Evaluating Standardized Corporate Branding Across Countries - Meierer, Markus (Gabler, 2011)
Marketers have to understand how the information that consumers associate with a company and its products affects their responses to those products. Adressing this issue, Markus Meierer analyzes firstly if consumers from Germany, France, Romania, Russia, and the USA perceive an internationally standardized corporate brand homogenously as well as if a positive effect on consumers' product response exists. Secondly he investigates if consumers perceive corporate and product brand as reciprocally related across countries as well as how the direct and indirect effects of corporate and product branding on consumers' product response look like.